TELEMEDICINE, COST EFFECTIVENESS, AND PATIENTS SATISFACTION: A SYSTEMATIC REVIEW - Atmojo, Joko Tri; Sudaryanto, Wahyu Tri; Widiyanto, Aris; Ernawati, Ernawati; Arradini, Dewi (Journal of Health Policy and Management, 2020)
Background: Telemedicine has been practiced since 1960. The objective of telemedicine was to establish feasible interactive telecommunication for medical diagnosis and treatment of patients at remote sites. Nowadays, with healthcare costs on the rise, telemedicine is increasingly being seen as a strategy for healthcare organizations to make cost-saving. This study aimed to explore the opportunity of telemedicine utilization in cost savings to patients and the health care system.Subjects and Method: A systematic review was conducted by searching the published articles from Pubmed, MEDLINE, EMBASE, CINAHL, and Science Direct databases. Keywords for this study were ?telemedicine? AND ?patient saticfaction?, ?telemedicine? AND ?cost-utility and cost-effectiveness?, ?telemedicine? AND ?systematic review?, and ?telemedicine? AND ?meta analysis?. The data were analyzed by PRISMA flow diagram.Results: 8 articles were selected for this study. These studies reported that telemedicine utilization in dermatology, radiology, pediatrics, and intensive care unit (ICU) rooms reduced health cost by 56% and patients travel cost to health care by 94%. Telemedicine advantages for patients were reduced transportation time or cost, eliminated time off of work, on-demand option, and reduced time in the waiting room, so that it can increase patient?s satisfaction. A study reported that telemedicine utilization at the pediatrics department increased hospital?s revenue by USD 101,744 per year.Conclusion: Telemedicine is an alternative health care to generate cost savings for patient and hospital and it can increase patient?s satisfaction.Keywords: Telemedicine, cost effectiveness, patient satisfactionCorrespondence: Joko Tri Atmojo. School of Health Sciences Mamba'ul 'Ulum, Surakarta, Jl. Ring Road Utara, Tawangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: jokotriatmojo1@gmail.com. Mobile: 08139331900Journal of Health Policy and Management (2020), 5(2): 103-107https://doi.org/10.26911/thejhpm.2020.05.02.02